Influencia de los medios digitales en la educación virtual de los adolescentes del Recinto Bimbe del Toachi, 2021 - Verdesoto Pinargote, Pamela Rubi (2021)
The present research was carried out in the Bimbe del Toachi enclosure of the Parish, Santa María del Toachi of the Santo Domingo de los Tsáchilas canton, through a descriptive study it was sought to investigate what is the influence of digital media on the virtual education of adolescents of the aforementioned Enclosure. Since the beginning of the pandemic, the education system has undercame harsh changes, one of them was the application of virtual education models applied to students, where teachers, authorities, parents and students themselves have had to overcome numerous difficulties. These difficulties were increased in the rural areas of the country where already before the pandemic there was little access to digital media and tools applied to the learning process, so when migrating face-to-face classes to the virtual environment there was a great problem. Through the analysis of surveys applied to students and parents, it was possible to determine that there is an inappropriate use of digital media in virtual education by adolescents of the Bimbe del Toachi campus due to a low level of digital competence of both parents and students, this is partly a consequence of the lack of use of digital media in the education of rural institutions much before virtual education was implemented due to the Covid-19 pandemic. So it represented a great challenge of adaptation of students, parents and teachers to the virtual modality and that in many aspects have not been able to overcome even these problems. Therefore, it is essential that both adolescents and parents are informed about digital media and their uses since these will be of great importance when face-to-face classes are resumed, because in future educational models it is possible that the use of digital media will be used as a necessary complement in the educational process.